Comparative Efficacy and Safety of Tirzepatide versus Semaglutide: A Systematic Review and Meta-Analysis with Cardiometabolic Implications - Khawar, Muneeb; Baba, Azhar Hafiz; Akhtar, Rameez; Rawat, Anurag; Afzaal, Huzaifa Bin; Haq, Affan Ul; Khalid, Mazen Bin; Ghazi, Muhammad Anas; Awan, Jahanzaib; Kumar, Beesham; Kumar, Pershan; Gurram, Yamini Saraswathi (Nepal Journal of Epidemiology, 2026)
Background: Obesity and type 2 diabetes are significant global health problems. Tirzepatide, a dual GIP/GLP-1 receptor agonist, and semaglutide, a selective GLP-1 receptor agonist, are the top incretin therapy options, but their relative effectiveness and safety based on direct head- to -head studies have not been pooled. This meta-analysis aims to compare the efficacy and safety of tirzepatide versus semaglutide. Methods: PubMed, Embase, and ScienceDirect were searched up to February 2026 to find the articles. Mean differences (MD) and risk ratios (RR) were pooled using a random-effects model and heterogeneity was measured using I². Results: Three studies were included. Tirzepatide caused significantly greater reduction in weight than semaglutide (pooled MD = −5.19 kg, 95% CI: −7.96 to −2.42; p = 0.0002; I² = 88.5%) and increased the possibility of ≥10% weight loss (pooled RR = 1.50, 95% CI: 1.15–1.96; p = 0.0069; I² = 86.3%). No significant difference was observed in any adverse events, or gastrointestinal events; however, there was a greater number of serious adverse events with tirzepatide (RR = 1.83, 95% CI: 1.18-2.85; p = 0.007). Conclusion: Tirzepatide can provide better weight loss than semaglutide with relatively similar safety, except that serious adverse events were more frequent. Studies with long follow-up are required to confirm the cardiovascular safety.